DURATION OF STRUCTURIZATION OF BIOLOGICAL FLUIDS IN NON-INVASIVE DIAGNOSTICS OF THE INFLAMMATORY PROCESS OF THE NASAL CAVITY AND PARANASAL SINUSES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
A new method for non-invasive diagnosis of chronic rhinosinusitis has been developed. The time of structurization of the solid phase of biological fluid was used as a diagnostic criterion.